Uso das tecnologias de informação e comunicação (TICs) no ensino do programa de educação de jovens e adultos (PROEJA) - (:unkn) unknown (Brasil, 2024)
The use of Information and Communication Technologies (ICTs) in the classroom can no longer be neglected or restricted. On the contrary, it should be embraced and explored in pedagogical practices to promote effective teaching. This article seeks to investigate how the use of ICTs can contribute to improving the teaching process in PROEJA, emphasizing the possibilities and benefits that these tools provide for pedagogical practice, as well as highlighting the importance of teachers' digital training. In this research, the main references were: Ritter (2015), Santos (2016), Stamberg et al. (2019), Alvarenga et al. (2021), and Costa (2021). Methodologically, this study is a bibliographic research, which demonstrates, in its results, that technologies promote more meaningful learning and offer support for more effective pedagogical practices. However, the lack of digital training among teachers prevents many from using these technologies in the classroom.
Keywords: Tecnologia de Informação e Comunicação; Information and communication technologies; Ensino; Teaching; Educação; Education; Proeja; Proeja; CNPQ::OUTROS